Improvement of temperature dependence of carrier characteristics of quantum dot solar cell using InN quantum dot - Al Humayun, Md. Abdullah; Khan, Sheroz; Alam, A. H. M. Zahirul; Yaacob, Mashkuri; AbdulMalek, MohamedFareq; Rashid, Mohd Abdur (www.ijrer.org, 2017)
Improvements of temperature dependence of certain characteristics of quantum dot solar cell using InN as active material of the device structure has been reported in this paper. A numerical analysis of temperature dependence of different parametric characteristics related to carriers within a quantum dot solar cell has been carried out in this research work. Numerical analysis of these solar cell features have been performed using Group-III Nitride trios namely GaN, AlN and InN quantum dot as active layer material of solar cell structure. Among different parameters of quantum dot solar cell: drift length and the diffusion length have been analyzed along with the power loss of the carriers to complete the whole process. In this present research work effect of temperature on the characteristics of these parameters has been analyzed using mathematical approach. Numerical results obtained are compared for preferential outcomes. It is revealed from the comparison results that only the drift length of the carrier has been increased but the diffusion length and the power loss of the carriers have been minimized using InN quantum dot in the active layer of solar cell. Hence InN is the auspicious material to fabricate solar cell in upcoming decades.